The book of books: Biblical interpretation, literary culture, and the political imagination from Erasmus to Milton - Fulton, Thomas (University of Pennsylvania Press, 2021)
This book examines the process of recovery, reinterpretation, and reuse of scripture in the early modern political imagination. It focuses in particular on the literary and cultural transformations of the biblical text for political purposes. It thereby attends to Hobbes' concern in "Behemoth" that independent scriptural reading led to the dissolution of authority by seeking to understand what role the Bible had in shaping early modern political thought. But most importantly, this study seeks to understand how, precisely, it played this role: what hermeneutic and practical procedures enabled early modern English readers to transform this supremely authoritative text for their use? How did certain imperatives in reading - such as literalism, or whatever we might call their actual method - shape or impede this transformation? To get at the most common, most everyday form of reading, and the most immediate transition from biblical text to cultural discourse, the author is drawn in particular to the apparatus surrounding the text, the interpretive paratext and marginal annotations. Naomi Tadmor's "Social Universe of the English Bible" has attributed the extraordinary success of the English Bible to the degree to which the translated text Anglicized the ancient Hebrew and Greek, so that more than simply translated, the text was "slightly moulded" to conform to an English framework, and "rendered in terms that made sense to people at that time." Biblical annotations take this process of molding still further, as they had far greater liberty than the translated text to draw a passage closer to a meaning and context germane to its readers. The author's interest here is not only in the content and function of biblical annotations, but also in what occurs in the space that they represent, an interface between the ancient code of biblical meaning and the currency of the early modern world